Materials, use and contaminated interaction - Baxter,WL; Aurisicchio,M; Childs,PRN (Materials & Design, 2015)
Materials help communicate meaning to users. This meaning changes with time as the object transforms due to use. Through a two-phase study, this research develops new understanding of how people appraise used objects and the mechanisms driving contamination—the aversion that one has towards engaging with used objects. In the first phase, observations of indicators of use were collected from participants in order to develop a general typology for indicators of use and deduce the sensorial properties of used objects. In the second phase, these observations were analysed to isolate the data, which caused feelings of aversion. The subset of observations marked with aversion was labelled as contaminated. Further analysis revealed three mechanisms driving contamination—hygiene, utility, and territory—presented together as the HUT contamination model. Sensorial properties from the first study were mapped to contamination mechanisms and properties most frequently contributing to contamination were identified. The properties contributing to the various contamination mechanisms differ significantly. Hygienic contamination typically results from transient object states, utility contamination from permanent changes to object characteristics, and territorial contamination from object settings and contextual factors. As expected, the majority of the indicators contributing to contamination are related to material properties. This work acts as a link between material selection and contaminated interaction with used objects.